2020
DOI: 10.21203/rs.3.rs-21863/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A tentacle for every occasion: comparing the hunting tentacles and sweeper tentacles, used for territorial competition, in the coral Galaxea fascicularis

Abstract: Background:Coral reefs are among the most diverse, complex and densely populated marine ecosystems. To survive, morphologically simple and sessile cnidarians have developed mechanisms to catch prey, deter predators and compete with adjacent corals for space, yet the mechanisms underlying these functions are largely unknown. Here, we characterize the histology, toxic activity and gene expression patterns in two different types of tentacles from the scleractinian coral Galaxea fascilcularis – catch tentacles (C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Putative toxin genes were identified using reciprocal best-BLAST hits as described in (Rachamim et al, 2015;Yosef et al, 2020) (Supplementary Table 14). Differential expression of genes coding for known biomineralization-related proteins from S. pistillata skeleton or the calicoblastic layer were examined (Puverel et al, 2005;Drake et al, 2013;Mass et al, 2013;Zoccola et al, 2015;Peled et al, 2020) (Supplementary Table 16).…”
Section: Focused S Pistillata Gene Analysesmentioning
confidence: 99%
“…Putative toxin genes were identified using reciprocal best-BLAST hits as described in (Rachamim et al, 2015;Yosef et al, 2020) (Supplementary Table 14). Differential expression of genes coding for known biomineralization-related proteins from S. pistillata skeleton or the calicoblastic layer were examined (Puverel et al, 2005;Drake et al, 2013;Mass et al, 2013;Zoccola et al, 2015;Peled et al, 2020) (Supplementary Table 16).…”
Section: Focused S Pistillata Gene Analysesmentioning
confidence: 99%
“…For example, the assassin bug Pristhesancus plagipennis and the cone snail Conus geographus produce distinct venoms specialised for predation and defence [ 46 , 47 ]. Differences in toxin expression across sweeper and feeding tentacles in corals can likewise be explained by the discrete roles of these two structures in intraspecific combat and prey capture, respectively [ 24 ]. While ecological interactions have minimal impact on the toxin gene complement in cnidarian species, they are known to function as keys drivers of toxin gene expression [ 14 , 25 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both catch and sweeper tentacles are specialised for agonistic encounters with competitors, causing necrosis in other polyps, and are morphologically distinct from feeding tentacles [ 20 , 22 , 23 ]. A recent investigation of gene expression in sweeper and feeding tentacles in the stony coral Galaxea fasicularis revealed that toxin genes are differentially expressed across the two tentacle subsets [ 24 ] indicating that venom composition may vary across tentacle types when they fulfil distinct ecological functions. We surmised that toxin expression might similarly differ in a tentacle-specific manner in sea anemones, given that they also possess functionally distinct tentacle subsets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a s i g n ifi c an t d ow n -r e g u l a t i on o f t h e e x p r e s s i o n o f nematogalactin and minicollagen-1, essential for nematocyst formation (Beckmann and Özbek, 2012) is observed at one week, and becomes more prominent over time (Figure 6B (7), ( 8)), supporting down-regulation of nematocyst formation. Nematocysts are essential for predation, defense and for territorial aggression (Yosef et al, 2020), therefore these results could indicate that prolonged deoxygenation enhance the corals' dependence on symbiosis-derived components and reduce its predation efforts.…”
Section: Acclimation To Deoxygenation Includes Enhanced Expression Of...mentioning
confidence: 95%